PENGUKURAN DAN PENILAIAN DALAM EVALUASI PEMBELAJARAN - Rona Rona (Cross-border, 2018)
Learning is the first step -hat must be taken to get the final result of the learning that has been applied. With the existence of learning, one can find out the success of students during the gap process that is being carried out, especially in elementary schools. The end result of this learning becomes one of the educational institutions, namely getting a good final result and in accordance with the purpose of learning. To find out the learning outcomes obtained, educators need to carry out what is called measurement and assessment of the learning outcomes. Measurement and assessment is very important for a teacher during the learning process.